2018
DOI: 10.1016/j.pediatrneurol.2017.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia in Children With Arterial Ischemic Stroke: Prevalence and Risk Factors

Abstract: Dyslipidemia and hypertriglyceridemia may be more prevalent in children with arterial ischemic stroke compared with stroke-free children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…A study that included children in the International Pediatric Stroke study showed that dyslipidemia was more common in children with arterial ischemic stroke compared to the data from the National Health and Nutrition Examination Survey (NHANES) (38.4% vs. 21%), and that 44.5% of children and 32.9% of adolescents with arterial ischemic stroke had hypertriglyceridemia, suggesting that the prevalence of dyslipidemia, including hypertriglyceridemia, might be higher in children with arterial ischemic stroke than in the general population 24,31…”
Section: Hypertriglyceridemia In Children and Adolescentsmentioning
confidence: 95%
“…A study that included children in the International Pediatric Stroke study showed that dyslipidemia was more common in children with arterial ischemic stroke compared to the data from the National Health and Nutrition Examination Survey (NHANES) (38.4% vs. 21%), and that 44.5% of children and 32.9% of adolescents with arterial ischemic stroke had hypertriglyceridemia, suggesting that the prevalence of dyslipidemia, including hypertriglyceridemia, might be higher in children with arterial ischemic stroke than in the general population 24,31…”
Section: Hypertriglyceridemia In Children and Adolescentsmentioning
confidence: 95%
“…The study by Sarecka-Hujar et al demonstrated that about 40% of children with arterial ischemic stroke had hypertriglyceridemia [ 67 ]. Moreover, the data from the International Pediatric Stroke Study (IPSS) demonstrated that 41% of children with arterial ischemic stroke had elevated levels of TG, whereas 36% of children were dyslipidemic [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…In each patient and healthy subject the status of dyslipidaemia (either TC ≥ 200 mg/dL, or HDL < 40 mg/dL, or non-HDL ≥ 145 mg/dL) and hypertriglyceridemia (for children aged up to 9 years TG ≥ 100 mg/dL, and for children aged 10–19 years, TG ≥ 130 mg/dL) were established following the Sultan et al [ 21 ] recommendations. The following intervals for lipid ratios were used: LDL/HDL normal < 3, borderline 3–4, and high > 4; TC/HDL normal < 4, borderline 4–5, and high > 5; TG/HDL normal < 3, and above normal > 3.…”
Section: Methodsmentioning
confidence: 99%